THE EFFECT OF WEED MANAGEMENT USING HERBICIDE ON CORN RESULTS (Zea mays L) - fitria; Nana Trisna Mei Br Kabeakan; Nurhajijah (Universitas Medan Area, 2023)
Weeds are undesired plants to grow so weed management is expected to overcome losses caused by weeds. One way to manage weeds using herbicides is the chemicals used for weed management in plants. This study aims to determine the influence of weed management using herbicides on corn yields. The research was conducted in Sekoci Village, Besitang District, Langkat Regency, North Sumatra in April-June 2021. This study used a non-factorial Randomized Block Design (RBD), with 4 treatments and 3 replications, namely contact, systemic, weeding and weeds without management. The results showed that herbicide management significantly affected 100 seed weight, cob weight per plot and seed weight per plot, but had no significant effect on weed without management. It indicates that the treatment of weed management using herbicides affects plant growth and yield. Weed management for farmers is very important to prevent competition for nutrients between weeds and corn.